Inspeksi Kesehatan Lingkungan dalam menjaga sanitasi rumah di lingkungan UPT Puskesmas Tembuku I Bangli - Widyasari, Ida Ayu Putri Genta; Steviani, Ni Kadek Meisy (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2024)
This community service aims to evaluate the role of environmental health inspections in maintaining home sanitation in the UPT Puskesmas Tembuku I Bangli area, in accordance with the Minister of Health Regulation Number 13 of 2015. This study used a descriptive observational method with data collection from the puskesmas during 2023. Data were collected through healthy home surveys on 50 households in the puskesmas working area, counseling, and direct inspections to patients' homes, as well as posyandu activities and health counseling in schools. The results showed that 90% of the houses in Tembuku Village met the requirements of a healthy home, while the other 10% did not meet the requirements. Some of the problems found include inadequate ventilation, improper waste water disposal, and residents' habits of not maintaining home hygiene. These conditions can increase the risk of environment-based diseases such as ARI. The conclusion of this study confirms the importance of improving house components, sanitation facilities, and occupant behavior to achieve optimal sanitation. These results are expected to contribute to the improvement of environmental health and home sanitation programs in Indonesia, especially in the UPT Puskesmas Tembuku I Bangli area.